The Influence of Field Work Practices on Entrepreneurial Interests of Class XII Students of the Online Business and Marketing Department at Perintis 1 Vocational High School, Depok - Adha, Fani; Narsih, Dwi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Research Objectives to determine the Effect of Field Work Practices Against the Interest in Entrepreneurship of Class XII Students of the Online Business and Marketing Department at Perintis 1 Vocational School, Depok. The population of this study are students of class XII SMK Perintis 1 Depok, totaling 70 learners. The total sample of 41 students was taken using simple random sampling. Method of collecting data using observation, questionnaire (questionnaire) and documentation. Results Simple Linear Regression Analysis research Y=0.685+0.996X, where constant value (a) or a fixed value of 0.685, meaning at the time of influence field work practices equal to 0, then the interest in entrepreneurship of 0.685 and if ?=0.996, it means that every 1% increase in practice field work, then the interest in entrepreneurship will also increase by 0.996. This shows that there is an influence between field work practices and entrepreneurial interest. Correlation coefficient of 0.789 indicates there is strong relationship between fieldwork practice and interest entrepreneurship. The coefficient of determination is 0.6225 which means 62.25% of this variable affects the interest in entrepreneurship while the remaining 37.75% is contributed by other factors, such as factors that come from the family environment, environment Education and community environment. Results obtained from hypothesis testing which shows the value of ?ℎ????? > ?????? (8.024 > 1.684) which states that there is an influence between work practices field on the interest in entrepreneurship of class XII students majoring online business and marketing at SMK Peintis 1 Depok. Field Work Practices, Interest in Entrepreneurship